Interpersonal Communication Of Caregivers In Shaping The Attitude Of Independence Of Children With Special Needs In The Social Institution For The Blind Amal Mulia City Of Bengkulu - Rizka Nurwitami; Lisa Adhrianti; Neneng Cucu Marlina (Eduvest - Journal of Universal Studies, 2024)
This research aims to find out and understand the interpersonal communication of caregivers in forming an attitude of independence for ABK at the Bina Netra Amal Mulia Social Home in Bengkulu City, as well as to determine the motives and goals of caregivers in working. Children who live in social institutions really need a substitute role for their parents. As time goes by, the child's communication context will be determined by the caregiver. This research is qualitative research with a phenomenological approach. The data in the research were collected using interview, observation and documentation techniques. The theory used is interpersonal communication theory with a humanistic approach from Joseph A. DeVito, and social phenomenology theory from Alfred Schutz to see motives, causes and goals. The findings in this research show that interpersonal communication between caregivers in forming an attitude of independence with ABK, the aspect of openness plays a big role in interpersonal communication between caregivers and ABK in this social institution, this aspect of openness can be the first step in interpersonal communication that can run smoothly in the future . There are obstacles when caregivers carry out interpersonal communication with ABK, these obstacles are in the form of semantic barriers, physical barriers and psychological barriers. The motives for working for caregivers in social institutions have different backgrounds. Even though they have different work backgrounds have the same goal, namely, apart from earning money for family needs, caregivers also aim to worship, do charity and be useful.